'In my end is my beginning': Peter Grimes and Death in Venice. (March 2022) - Lambert, Sterling
Abstract: Benjamin Britten, gravely ill at the time of its composition, was surely aware that Death in Venice would be his last opera, and it is not surprising that the work should make reference to his first opera, Peter Grimes, as if to bookend his entire operatic career, and survey the enormous distance he had travelled, as a hallmark of what might be considered the composer's late style. Even so, the dramatic and musical relationships between the two works are unusually extensive. Both operas concern an outsider at odds with the society around him, in a strange reflection of the composer's particular situation as he wrote each work. Each is set in a place particularly special to the composer, where land borders sea in a metaphor for the boundary between life and death. Finally, the protagonist's interactions with a mysterious silent boy in each case hints at a part of Britten's character that dared not speak its name. These dramatic correspondences are paralleled in important musical connections between the operas, despite their ostensibly very different musical languages. Britten's final opera could therefore be understood to exemplify the famous words borrowed by T.S. Eliot from Mary, Queen of Scots: 'In my end is my beginning', an appropriate concept given the degree to which Britten was occupied with Eliot's verse at this time.